Sustainable Delivery Model Selection using AROMAN Approach - Dobrodolac, Momčilo; Bošković, Sara; Jovčić, Stefan; Lazarevic, Dragan (My University, 2024)
The development of electronic commerce has resulted in an increase in the number of shipments in their transfer systems. Delivery companies strive to respond to emerging situations, meet customer needs, and achieve profit through the optimization of their operations. The imperative is to establish a delivery system that is in line with the principles of sustainable development. This paper defines the task of choosing a sustainable model for shipment delivery and proposes the AROMAN method for its resolution. The applicability of the proposed method is demonstrated by solving the defined task in the territory of the city of Belgrade.
Výběr modelu udržitelné dodávky pomocí přístupu AROMAN
Keywords: Sustainable; Delivery; Model; Selection; AROMAN; udržitelnost; doručování; model; výběr; AROMAN